Distinct mRNA and protein interactomes highlight functional differentiation of major eIF4F-like complexes from Trypanosoma brucei - Bezerra, Maria; Moura, Danielle M. N.; Freire, Eden R.; Holetz, Fabiola B.; Reis, Christian R. S.; Monteiro, Tallyta T. S.; Pinto, Adriana R. S.; Zhang, Ning; Rezende, Antonio M.; Pereira-Neves, Antonio; Figueiredo, Regina C. B. Q.; Clayton, Christine; et al. (Frontiers in molecular biosciences, 2022)
Gene expression in pathogenic protozoans of the family Trypanosomatidae has several novel features, including multiple eIF4F-like complexes involved in protein synthesis. The eukaryotic eIF4F complex, formed mainly by eIF4E and eIF4G subunits, is responsible for the canonical selection of mRNAs required for the initiation of mRNA translation. The best-known complexes implicated in translation in trypanosomatids are based on two related pairs of eIF4E and eIF4G subunits (EIF4E3/EIF4G4 and EIF4E4/EIF4G3), whose functional distinctions remain to be fully described. Here, to define interactomes associated with both complexes in Trypanosoma brucei procyclic forms, we performed parallel immunoprecipitation experiments followed by identification of proteins co-precipitated with the four tagged eIF4E and eIF4G subunits. A number of different protein partners, including RNA binding proteins and helicases, specifically co-precipitate with each complex. Highlights with the EIF4E4/EIF4G3 pair include RBP23, PABP1, EIF4AI and the CRK1 kinase. Co-precipitated partners with the EIF4E3/EIF4G4 pair are more diverse and include DRBD2, PABP2 and different zinc-finger proteins and RNA helicases. EIF4E3/EIF4G4 are essential for viability and to better define their role, we further investigated their phenotypes after knockdown. Depletion of either EIF4E3/EIF4G4 mRNAs lead to aberrant morphology with a more direct impact on events associated with cytokinesis. We also sought to identify those mRNAs differentially associated with each complex through CLIP-seq with the two eIF4E subunits. Predominant among EIF4E4-bound transcripts are those encoding ribosomal proteins, absent from those found with EIF4E3, which are generally more diverse. RNAi mediated depletion of EIF4E4, which does not affect proliferation, does not lead to changes in mRNAs or proteins associated with EIF4E3, confirming a lack of redundancy and distinct roles for the two complexes.
Veröffentlicht: 7. Oktober 2022
Gesehen am 29.08.2023